Research capacity for childhood obesity prevention in Latin America: an area for growth. (July 2017) - Parra, Diana C.; Vorkoper, Susan; Kohl, Harold W.; Caballero, Benjamin; Batis, Carolina; Jauregui, Alejandra; Mason, Jessica; Pratt, Michael
Summary: Background: The rise of childhood obesity in Latin America calls for research capacity to understand, monitor and implement strategies, policies and programmes to address it. Objective: The objective of the study was to assess current research capacity in Latin America related to childhood obesity, nutrition and physical activity. Methods: We conducted a search of peer‐reviewed articles on childhood obesity in Latin America with at least one Latin American author from 2010 to May 2015. We coded 484 published articles for author affiliation, study subjects' nationality, research topic and study design and extracted a series of networks per research topic, study design and collaborating country for each of the countries. Results: Obesity is the most frequently explored topic. Nutrition and obesity are somewhat better developed compared with physical activity and sedentary behaviour. There are numerous observational and cross‐sectional studies, indicating either a lack of capacity required for more complex research or the extent of the problem and associated factors is still unknown. The low number of intervention studies and the near absence of policy articles suggest a void in research capacity. Conclusion: For childhood obesity, there is a clear need to build research capacity that documents the current state of the problem and design evidence‐based prevention and intervention efforts.